Natural colouring agents obtained from different plant sources applied to the pastry sector - Reis, Filipa S. (2018)
Given that some intolerance and allergic reactions have been associated with the consumption of artificial additives, in recent decades consumers have been choosing to ingest food containing natural alternatives [1,2]. The present work presents some preliminary results regarding the incorporation of natural colorants in products of the pastry industry. The juices of different natural matrices namely beet, blackberry and cherry were incorporated into a pastry product (at TecPan Lda.). The samples were divided into small sets, to evaluate the nutritional value, the microbial load and the parameters of color and pH over time. Here, we present the results of the first three months of storage of the pastry products. The values obtained were compared with control samples (without any natural/artificial colorant) and with products incorporated with an artificial colorant used by the company. Moreover, the products were stored, exposed and protected from light, in order to verify the stability of the additives, and the results were compared. The nutritional value of the samples remained practically unchanged over time, and no changes were observed regarding the microbial load of the samples. However, some variations were observed in the pH and color values. The products prepared with berry juices tended to present the highest pH values. Regarding the color parameter, products prepared without any coloring agent showed the highest L* values, whilst those prepared with the artificial colorant were less bright. In what regards a*, as expected, control products presented the lowest value. Concerning b*, the minimum values were registered in products prepared with the artificial colorant, and the maximum ones observed in control samples. Overall, the storage time did not induce any significant change in any case, and the results obtained from stored samples protected from light and exposed to light were very similar.